Effect of sm3+ concentration on physical properties of magnesium tellurite glasses containing silver nanoparticles - Mohammad Yusoff, Nurulhuda (TRANS TECH PUBLICATIONS, 2016)
A series of tellurite (TeO2) glass containing samarium (Sm2O3) and silver nanoparticles with a composition of (89.6-x)TeO2-10MgO-(x)Sm2O3-0.4AgCl with 0.2 ≤ x ≤ 1.0 mol% have been synthesized by a conventional melt quenching technique. The X-ray diffraction pattern verified the amorphous nature of glasses. A systematic study on the relationship between Sm2O3 concentration and the physical properties of the glass has been made. The effect on the progressive replacement of TeO2 by Sm2O3 on density, molar volume, refractive index and electronic polarizability has been investigated. The results show that density and ionic packing density are in the range of 4.91-5.04 g cm-3 and 0.444 – 0.455, respectively, increases as the amount of Sm2O3 is increased up to 0.8 mol% and decrease afterward. However, the molar volume which is in between, 29.59-30.26 m3 mol-1 decreasing as the amount of Sm2O3 is increased up to 0.8 mol% and increase thereafter. Meanwhile the refractive index which is deduced from optical energy band gap is found to possess a value in the range of 2.37 to 2.45 and electronic polarizability is in the range of 7.14-7.51Å3. All the results will be discussed with respect to the modification in glass composition.